Enhancing Impact for Key Leadership Domains - Mark Avery (Asia Pacific Journal of Health Management)
Significant operational and functional action domains require health, aged and social care leaders and managers’ expertise and responsibilities. Contemporary strategic; development and operational activities involving patient/client centred care; strategic vision articulation and alignment; financial performance; workforce management; effective communications; informatics challenges; enabling strong and positive organisational cultures as well as managing conflict and resistance to change are required and need to deeply focused on the context of clinical and social health care.....